749 Clinical profile and outcome of patients with Anderson–Fabry disease followed at a multidisciplinary cardiomyopathy centre. (8th December 2021) - Verrillo, Federica; Fumagalli, Carlo; Tassetti, Luigi; Zocchi, Chiara; Tanini, Ilaria; Baldini, Katia; Tomberli, Alessia; Zampieri, Mattia; Argirò, Alessia; Cappelli, Francesco; Girolami, Francesca; Limongelli, Giuseppe; et al.
Abstract: Aims: Anderson–Fabry disease (AFD) is a rare genetic lysosomal storage disorder which often goes unnoticed until the onset of symptoms requires aggressive treatment. Prompt diagnosis remains crucial. Dedicated centres may offer a remarkable opportunity to develop early detection strategies and prompt appropriate multidisciplinary management. To describe the long-term outcomes of patients diagnosed with AFD followed at a national Cardiomyopathy Referral Center according to phenotype (clinical involvement vs. sub-clinical involvement). Methods and results: Consecutive patients visited at our Cardiomyopathy Unit from 1989 to 2020 with >1-year follow-up were retrospectively reviewed. Clinical involvement was defined by the presence of one among left ventricular hypertrophy (LVH)>15 mm, presence of conduction blocks or cardiac implantable electronic devices (CIED), atrial fibrillation, kidney disease (glomerular filtration rate <60 ml/min/m 2, dialysis or kidney transplant), stroke or transient ischaemic attack (TIA). Disease progression was defined by either de novo CIED implantation, de novo LVH > 15mm or increased IVS, de novo Stroke/TIA, or progression of kidney disease. Overall, 110 were diagnosed with AFD [first via α galactosidase (αGAL) activity and then confirmed via genetic exam], and 86 (78%) with >1-year follow-up were selected. Clinical involvement was present in 60 (70%) patients. Age at diagnosis was similar between patients with clinical and subclinical phenotype (42 ± 17 vs. 39 ± 15, P = 0.277). Patients manifesting clinical involvement compatible with AFD were more frequently men [ N = 25 (42%) vs. 4 (15%), P = 0.025] and probands ( P = 0.01). Overall, one organ involvement was present in 31 (52%) patients, two organ involvement in 24 (40%) patients, and three organs in 5 (8%). A total of 46 (77%) patients were referred for enzyme replacement therapy (ERT): 52% received agalsidase α, 26% agalsidase β, and 22% migalastat. Among those with a clinical involvement not on ERT, nine (15%) were scheduled for ERT initiation, three (5%) were considered old for ERT, one (1.5%) refused ERT, and one (1.5%) had an allergic reaction to ERT. At 7 (3–12) years follow-up, both study cohorts manifested signs and symptoms of disease progression, although its incidence was higher in patients with clinical involvement [ N = 28 (47%, 4.7%/year) vs. N = 4 (15%, 1.5%/year), in clinical vs. subclinical involvement, respectively, P = 0.01]. The main causes for diseases progression were increase in LVH (28%), de novo LVH (13%), progression of kidney disease (7%), and CIED implantation (5%). All patients with disease progression in the subclinical involvement group had been diagnosed with family screening; among these, two were men and one had a late onset phenotype. Three developed LVH > 15mm and one kidney disease. Conclusions: Clinical involvement in AFD is frequent irrespective of age at diagnosis, being present in more than 1-in-2 patients at baseline. Prompt referral to dedicated centres is warranted for appropriate care as disease may progress in both patients with and without initial clinical involvement despite optimal medical management.